2014
DOI: 10.1177/1754337114547555
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanics of slalom water skiing

Abstract: Water skiing has received little attention in research literature and has not utilized recent advancements in analysis technology like other highly dynamic sports. In this study, six advanced slalom skiers were recruited to test four different high-performance ski designs, with the goal being to detect performance differences achieved between ski designs and between skiers during slalom turns. To aid the analysis of the resulting activity data, a series of 11 quantitative performance parameters were defined an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 3 publications
1
4
0
2
Order By: Relevance
“…Previous research reported that water skiers can reach on average 127% of the boat speed [22]. For a typical water ski competition boat speed of 16 m/s (58 kph), a water skier would likely reach 20 m/s (72 kph); this is consistent with the speeds reported in other research [23]. For this testing, water entry speed was limited by the height of the test facility.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…Previous research reported that water skiers can reach on average 127% of the boat speed [22]. For a typical water ski competition boat speed of 16 m/s (58 kph), a water skier would likely reach 20 m/s (72 kph); this is consistent with the speeds reported in other research [23]. For this testing, water entry speed was limited by the height of the test facility.…”
supporting
confidence: 87%
“…These differences may have been generated by the shape at the occipital edge of the helmet and the posterior protrusions, and not the venting. While a water sport helmet affected the loads produced in the Pelvis-First water impacts, the predicted speed needed to reach injury level (44 m/s) was well above the highest speeds in water skiing and wakeboarding (under 22 m/s) [22,23].…”
mentioning
confidence: 94%
“…Thus, various DWS methods are taught, but whether a sit-skier is starting from the water independently, using an instructor-assisted start technique (e.g., arm-lock, straddle or side-skier methods), or using learning aids (e.g., “ deep V ” handle, “ Edge Triple Bar ”, “ boom ”) [8], there is always the need to reduce the required grip force and lessen the impact of fatigue [9]. Up to now, most studies in the field of standing waterskiing have focused on the biomechanical characteristics and physiological demands of slalom [5,7,1013] and have adequately described a strength and conditioning program [14]. Despite its relevance from a performance point of view, the nature of the internal training load (TL) when starting and performing the repeated movements of slalom waterskiing remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…No obstante, el buen desempeño durante las pasadas de slalom está limitado en última instancia por el esfuerzo específico en el agarre manual del palonier (Barnett & Ziemba, 2009;Rosa et al 2016); es decir, por la fuerza de prensión manual (FPM), entendida como la fuerza isométrica máxima ejercida sobre un dinamómetro por los músculos de la mano y del antebrazo (Cabeza-Ruiz et al, 2009), y la resistencia de agarre, definida como la capacidad para sostener el agarre durante un periodo de tiempo (Barnett & Ziemba, 2009). La valoración de la FPM es frecuente en deportes donde un agarre isométrico cumple un rol importante, como la escalada, el judo o la vela (Barrionuevo Vallejo, Fructuoso Rosique, Hernández Ros, & Martínez González-Moro, 2007;Bonitch-Góngora, Bonitch-Domínguez, Padial, & Feriche, 2012;Carballeira & Iglesias, 2007;Iglesias, Clavel, Dopico, & Tuimil, 2003;Watts, Newbury, & Sulentic, 1996), pero no ha recibido atención investigadora en el esquí náutico, en el cual resulta difícil estandarizar las condiciones de entrenamiento o competición para el registro de datos cuantitativos experimentales (Bray-Miners, Runciman, Monteith, & Groendyk, 2015). Por ello, el objetivo de este estudio fue determinar los efectos agudos sobre la FPM de la práctica de esquí náutico en la disciplina de slalom en esquiadores sentados con paraplejia.…”
Section: Introductionunclassified